2023
DOI: 10.3390/nu15061444
|View full text |Cite
|
Sign up to set email alerts
|

Vegan Diet Is Associated with a Lower Risk of Chronic Kidney Disease in Patients with Hyperuricemia

Abstract: Hyperuricemia is a well-known risk factor for chronic kidney disease (CKD). Little is known about whether a vegetarian diet is associated with a lower risk of CKD in patients with hyperuricemia. From 5 September 2005, to 31 December 2016, we retrospectively included clinically stable patients with hyperuricemia who received health check-ups at Taipei Tzu Chi Hospital. All participants completed a dietary habits questionnaire to determine whether they were omnivorous, lacto-ovo vegetarian, or vegan. CKD was def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…In primary prevention of CKD, plant-based diets appear better than omnivorous diets because, as we have seen, they protect against the risk of developing hypertension, diabetes, obesity, and dyslipidaemia [20][21][22][23][24][25][26][27][28][29][30][31][32][33], which are well-known risk factors of kidney disease; some observational studies as well as a recent systematic review have also suggested a protective role against the development and progression of CKD [41][42][43][44][45][83][84][85]. Furthermore, as mentioned before, plant-based diets are more aligned with the nutritional indications of the WHO (Word Health Organization), while the usual western diet is too rich in proteins, sodium, and phosphorus [105].…”
Section: Possible Advantages Of Plant-based Low-protein Dietsmentioning
confidence: 97%
See 1 more Smart Citation
“…In primary prevention of CKD, plant-based diets appear better than omnivorous diets because, as we have seen, they protect against the risk of developing hypertension, diabetes, obesity, and dyslipidaemia [20][21][22][23][24][25][26][27][28][29][30][31][32][33], which are well-known risk factors of kidney disease; some observational studies as well as a recent systematic review have also suggested a protective role against the development and progression of CKD [41][42][43][44][45][83][84][85]. Furthermore, as mentioned before, plant-based diets are more aligned with the nutritional indications of the WHO (Word Health Organization), while the usual western diet is too rich in proteins, sodium, and phosphorus [105].…”
Section: Possible Advantages Of Plant-based Low-protein Dietsmentioning
confidence: 97%
“…Similarly, another study, involving a population of nearly 15,000 people enrolled in the Atherosclerosis Risk in Community Study (ARIC) group, showed that high adherence to a plant-based diet correlated with a decreased incidence of chronic kidney disease as well as a reduced decline in kidney function over time [29]. In a recent observational study in Taiwan, 3618 patients with hyperuricemia were recruited, and a vegan diet was associated with a 31% lower risk of CKD [42].…”
Section: Pbds' Effects On Ckd Riskmentioning
confidence: 99%
“…3 CKD is related to an increase in all-cause and cardiovascular mortality, 4 and patients who survived morbidities would still have to live for years with disability. 5 Instead of treating the illness, it is more crucial to stop CKD from developing.…”
Section: Introductionmentioning
confidence: 99%
“… 28 , 34 - 36 Vegetarian and vegan diets have demonstrated reduced CKD prevalence in cross-sectional studies. 37 , 38 Plant-based diets are also associated with reduced risks of other noncommunicable diseases such as heart disease, type 2 diabetes, and cancer, as well as all-cause mortality. 18 , 39 …”
Section: Introductionmentioning
confidence: 99%